ASUHAN KEPERAWATAN PADA KELUARGA An. Hi PENDERITA STUNTING DENGAN MASALAH DEFISIT NUTRISI - Pane, Efi Irwansyah; Juli Asmara, Sinta; Lubis, Josep Kristian (Jurnal Keperawatan Dan Kesehatan Holistik, 2025)
Stunting is a disorder of growth and development of children due to chronic malnutrition and recurrent infections, which is characterized by their length or height being below standard. Stunting toddlers are included in chronic nutritional problems caused by many factors such as socio-economic conditions, maternal nutrition during pregnancy, illness in infants, and lack of nutritional intake in infants. This writing method uses a case study method with a family nursing care approach to An.Hi, a stunting patient with 1 child patient. Data collection uses family nursing care which includes assessment, diagnosis, intervention, implementation and evaluation. Based on the analysis of data obtained from the assessment, there is one priority diagnosis, namely nutritional deficit related to the inability to absorb nutrients, characterized by a weight loss of at least 10% below the ideal range. The supporting factor in this case study is the willingness of all family members to improve An.Hi's nutritional status. It is expected that the family should be able to recognize the health problems of their family members, then the family can decide what actions should be taken immediately, caring for sick family members.